The Anemic Newborn at Birth: From Diagnosis to Treatment - Petrolini, Chiara; Chiara, Lembo; Chiara, Brugnoli; Mario, Staccioni; Buonocore, Giuseppe; Perrone, Serafina (Current Pediatric Reviews, 2023)
Neonatal anaemia is a very frequent clinical condition that may be due to apparent or not evident blood loss, decreased red blood cells (RBCs) production, or increased destruction of RBCs. RBCs transfusion criteria are clearly defined by several national and locally agreed guidelines. However, it is not possible to define a unique cut-off to guide clinicians' transfusion practice, which needs a multiparametric analysis of demographic variables (gestational age, postnatal age, birth weight), clinical evaluation, conventional and new generation monitoring (such as echocardiography and near-infrared spectroscopy). Unfortunately, few tools are available in the delivery room to help neonatologists in the management of newborn with acute anaemia. Early volume replacement with cristalloids and RBCs transfusion could be life-saving in the delivery room when a hypovolaemic shock is suspected, but the use of un-crossmatched whole is not risk-free nor easily available in clinical practice. Placental transfusion could be an extremely effective and inexpensive method to increase haemoglobin (Hb), to improve oxygen delivery, and to increase cardiac output with a reduced need for RBCs transfusions, a reduced risk of intraventricular haemorrhages, and an improved survival of the newborn.
Keywords: red blood cell transfusions